RADIOCARBON DATING OF THE HISTORIC EMPEROR’S BEECH FROM MUNCEL, BAIA DE ARIES, ROMANIA - PATRUT, Adrian; BOCOS-BINTINTAN, Victor; PATRUT, Roxana T.; PARTILA, Doriana; RATIU, Ileana-Andreea; RAKOSY, Laszlo; VON REDEN, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of the historic Emperor’s Beech (Fagul Împăratului) from Muncel, Baia de Arieş, Romania. Two wood samples were collected from the large tree, out of which four segments were extracted and analysed by AMS radiocarbon. The oldest dated sample segment had a radiocarbon date of 233 ± 18 BP, which corresponds to a calibrated age of 365 ± 5 years. This value suggests an age of 420 ± 20 years for the Emperor’s Beech. Thus, the historic beech started growing around the year 1600.